Optimization of Maduramicin Ammonium-Loaded Nanostructured Lipid Carriers Using Box-Behnken Design for Enhanced Anticoccidial Effect against Eimeria tenella in Broiler Chickens - Yan Zhang; Runan Zuo; Xinhao Song; Jiahao Gong; Junqi Wang; Mengjuan Lin; Fengzhu Yang; Xingxing Cheng; Xiuge Gao; Lin Peng; Hui Ji; Xia Chen; et al. (MDPI AG, 2022)
Maduramicin ammonium (MAD) is one of the most frequently used anticoccidial agents in broiler chickens. However, the high toxicity and low solubility of MAD limit its clinical application. In this study, MAD-loaded nanostructured lipid carriers (MAD-NLCs) were prepared to overcome the defects of MAD by using highly soluble nanostructured lipid carriers (NLCs). The formulation was optimized via a three-level, three-factor Box-Behnken response surface method. Then, the optimal MAD-NLCs were evaluated according to their hydrodynamic diameter (HD), zeta potential (ZP), crystal structure, encapsulation efficiency (EE), drug loading (DL), in vitro release, and anticoccidial effect. The optimal MAD-NLCs had an HD of 153.6 ± 3.044 nm and a ZP of −41.4 ± 1.10 mV. The X-ray diffraction and Fourier-transform infrared spectroscopy results indicated that the MAD was encapsulated in the NLCs in an amorphous state. The EE and DL were 90.49 ± 1.05% and 2.34 ± 0.04%, respectively, which indicated that the MAD was efficiently encapsulated in the NLCs. In the in vitro study, the MAD-NLCs demonstrated a slow and sustained drug release behavior. Notably, MAD-NLCs had an excellent anticoccidial effect against Eimeria tenella in broiler chickens. In summary, MAD-NLCs have huge potential to form a new preparation administered via drinking water with a powerful anticoccidial effect.